Price analysis of the english premier league soccer players according to their FIFA 20 statistics - Moya Villanueva, Gonzalo Rafael (2021)
On the basis of the premise that the videogame FIFA 20 measures correctly the abilities of professional soccer players, we built an econometric model with these measurements to identify which players would be over-priced and which ones under-estimated, comparing their quotings at the TransferMarkt website against the values assigned by our model based on their skills. We took a sample of the 14 players with more minutes on field that participated on the 2019-20 Premier League until the stoppage due to the pandemic (not including goalkeepers). As a result, we obtained that, although the clubs’ placement on the standings table had a more positive correlation with their staff quotings at TransferMarkt than with their abilities measured by FIFA 20, looking for discrepancies between price and value does indeed generate a window opportunity to build teams in a smart way, and thus achieve efficiency on hiring expenditures.